ANALISIS WACANA MEDIA PADA BROSUR ‘WASPADA DEMAM BERDARAH CEGAH DENGAN 3M PLUS’ - Indah Velayani; Ika Septiana (STKIP Subang, 2025)
This study aims to analyze how the media construct and represent social reality through discursive practices. Using a critical discourse analysis approach, the study examines textual structures, discourse production practices, and the social contexts underlying them. The research data consist of news texts published by national mass media within a specific period and are analyzed using qualitative analysis techniques.The findings indicate that the media are not neutral in conveying information; rather, they actively shape meaning through the choice of diction, sentence structures, the highlighting of certain actors, and the omission of others. The constructed discourse tends to reflect ideological interests and dominant power relations within society. These findings suggest that the media function as agents of social construction that influence how the public understands an event.This study is expected to contribute theoretically to communication studies and media studies, as well as to serve as a reference for the public to adopt a more critical stance toward media-produced discourse.